Penggunaan Multi Process Welding Machine Untuk Menunjang Kegiatan Praktikum Pengelasan Pada Laboratorium Pengelasan Kapal (Welding School) Sekolah Vokasi - Indro Dwi Cahyo (Jurnal Pengelolaan Laboratorium Pendidikan, 2022)
The existence of a laboratory is very necessary to fulfill curriculum a chievements. Because laboratory is a mandatory facility to hold any practical classes. Undip Vocational School of Marine Construction Engineering Technology Study Program is using the 2020th "Kampus Merdeka"  curriculum, in which one of the practical classes is welding and carried out at the Ship Welding Laboratory using a Multi-Process Welding Machine. The purpose of the welding practicum  provision is to find out the results of welding that carried out by students using data collection method and conducting experimental settings that are adjust ed to the welding data reading. Welding process using SMAW integration of amperage and voltage with due regard to the WPS procedure. From several samples of welding results, it can be seen that some parts may have welding defects.  Welding with the SMAW method using an E6013 electrode with a diameter of 2.6 mm, and with a plate thickness of 10 mm at 50 - 70 amperes, whilst for a 5 mm plateat 48 - 65 amperes, but also depends on the welding clock flown and position.